Balinese Cattle Cultivation in the Nandini Cattle Group in Balangan Kuwum Badung Village - Astiti, Ni Made Ayu Gemuh Rasa; Laksmi, Anak Agung Rai Sita; Eryani, I Gusti Agung Putu; Devani, Made Pradnyagitha Harum; Wadu , Yesaya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Kuwum Village, in Mengwi District, Badung Regency, Bali, is about 29 km north of Denpasar. Here, raising Bali Kereman cattle supplements farmers' income from farming and other jobs. Despite the potential profitability from meat, offspring, manure, and labor, the Nandini cattle group faces challenges. These include insufficient capital, inadequate feed, poor cattle maintenance, inefficient manure processing, and underdeveloped manure sales channels, hindering income maximization. The primary issue is low management capability in cattle maintenance. Effective cattle raising requires an ideal stable location, at least 10 meters from houses, accessible by vehicle, and near agricultural land, allowing sunlight. Quality seed selection, stable maintenance, and adequate feeding are essential. To address these challenges, methods such as presentations and demonstration plots for forage feeding and cage spraying are used. These activities aim to improve farmers' knowledge and practices, increasing cattle weight and farmers' income, ultimately achieving better welfare. Community Service activities have enhanced understanding and demonstrated proper maintenance, feeding, and cage spraying in the Nandini cattle group